Molecular Evidence for Multiple Infections as Revealed by Typing of Asaia Bacterial Symbionts of Four Mosquito Species - Chouaia, Bessem (American Society for Microbiology (ASM), 2010)
The recent increased detection of acetic acid bacteria (AAB) of the genus Asaia as symbionts of mosquitoes, such as Anopheles spp. and Aedes spp., prompted us to investigate the diversity of these symbionts and their relationships in different mosquito species and populations. Following cultivation-dependent and -independent techniques, we investigated the microbiota associated with four mosquito species, Anopheles stephensi, Anopheles gambiae, Aedes aegypti, and Aedes albopictus, which are important vectors of human and/or animal pathogens. Denaturing gradient gel electrophoresis (DGGE) analysis based on the 16S rRNA gene revealed the presence of several bacterial taxa, among which Asaia sequences were among the dominant in most of the samples. A collection of 281 Asaia isolates in cell-free media was established from individuals belonging to the four species. The isolates were typed by internal transcribed spacer (ITS)-PCR, tRNA-PCR, BOX-PCR, and randomly amplified polymorphic DNA (RAPD)-PCR, revealing that different Asaia strains are present in different mosquito populations, and even in single individuals.